The impact of organizational ergonomic risk factors on musculoskeletal disorders and driving fatigue towards near miss accident amongst Malaysian express bus drivers - Yusof, Hashim (2020)
Human error has been identified as the main contributing factors for the prevalence of Malaysian express bus accidents. However, studies on the underlying factors that contribute to error making decision by the express bus drivers are not widely addressed. Current studies either in Malaysia or overseas indicate that an organizational ergonomic risk factor has a significant influence on musculoskeletal disorder (MSDs) symptoms and driving fatigue which ultimately leads to the occurrence of near miss accidents. However, most of the studies are based on individual ergonomic stressors whereas the ergonomic stressors exists in groups or clusters in the transport system. The difference in this situation creates knowledge gaps that requires further research. Therefore, this study is designed to bridge the knowledge gap. The "Self-Reported" questionnaire was developed with some adaptation from previous research questionnaires. Data are collected from the purposive respondent (n = 278). The respondents are from four major express bus terminals in West Malaysia; Kuantan, Kuala Terengganu, Kota Bahru and Pudu Raya in Kuala Lumpur. The statistical package SPSS version 20+ and PLS-SEM methods are used to analyze the data. The research findings show that the working condition factors (WCF) and ergonomic workplace factors (EWP) formed the dominant determinants on musculoskeletal disorders (MSDs) symptoms, driving fatigue (DF) and near miss accident (NMA). However the organizational safety climate factor (OSCF) was least dominant. In transport industries the research findings contribute to an increase in understanding of organizational ergonomic risk factors as occupational hazards at workplaces. Hazards identification and hazards risk control management are very essential in determining safety at workplace.